A new concept of a rotating hollow fibre membrane module:impact of rotation on fine-bubble aeration. (29th April 2022) - Mahdariza, Fathul; Domingo Rimoldi, Ignacio; Henkel, Jochen; Morck, Tobias
Abstract: A new concept of a rotating membrane module in a membrane bioreactor (MBR) system was tested for its effect on oxygen transfer in clean water and wastewater. The membrane module consists of horizontally aligned hollow fibres connected to the vertically positioned permeate tube which rotates. The results indicated that oxygen transfer can be improved by up to 50% at the highest applied rotational speed (50 rpm) and that the additional energy demand required for the rotation can be compensated by the enhanced oxygen transfer. However, at the highest rotational speed (50 rpm), the fine bubbles bypassed the MBR module, and, consequently, could not contribute to any cleaning effect. The α -factors at different rotational speeds showed similar results. This indicates that the depletion was caused neither by surfactants nor by viscosity phenomena but rather by the floc/solid holdup of the sludge. HIGHLIGHTS: The novel membrane bioreactor configuration provides a promising result in oxygen transfer experiments. With the introduction of 50 rpm rotation, the oxygen transfer was improved by 50%. The floc volume was the main driver for oxygen transfer depletion. The additional energy demand for rotation can be compensated by the better oxygen transfer efficiency. Graphical Abstract